Book Review of “The Practice of Collaborative Counseling and Psychotherapy: Developing Skills in Culturally Mindful Helping” - Dixon, Sandra (Canadian Journal of Counselling and Psychotherapy, 2014)
The Practice of Collaborative Counseling and Psychotherapy: Developing Skills in Culturally Mindful Helping encourages active learning for readers by using reflections, vignettes, discussions, chapter summaries, and experiential exercises. Each story-like chapter is laden with rich insights on the counsellor-client relationship that is informed by relevant and current theoretical approaches to counselling practices. The book is written from a narrative perspective, which may be a drawback for those readers who find this approach to be esoteric. Nonetheless, Paré offers practical and theoretical skills framed within the narrative perspective.